The implementation of some regenerative practices to improve the sustainability of Latxa dairy sheep system - Mandaluniz N.; Pascual A.; Arranz J.; Ruiz R. (Innovation for sustainability in sheep and goats, 2019)
Land use and grazing management practices have changed during the last decades as a result of intensification. Some of the consequences are directly related to environmental impacts. Under this scenario, the assessment of the effect of different management practices is critical to improve the sustainability of landbased systems. The main objective of the current work was to determine the effect of some regenerative practices on productive and environmental parameters. Two essays were carried out with the experimental flock of Neiker during 2014 and 2015, with two grazing regimes: regenerative (RG) and free (FG). Soil, pasture and livestock samples and data were obtained during springs, and carbon footprint was estimated with data collected monthly before (2013) and after (2014-2015) the regenerative practices were implemented. According to the results, there were no differences on milk parameters (daily milk yield and composition) and livestock parameters (live weight and body condition score) due to grazing management. RG regime resulted in 8% higher amount of particulate organic matter in the soil and 10% greater amounts of harvested herbage. Moreover, the regenerative practices implemented reduced the carbon footprint in 10%. As conclusion, the regenerative practices implemented in the study seemed to be linked with an increase of harvested herbage and a reduction of carbon footprint without compromising livestock productive parameters.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)